f(x)=3-2x^3; g(x)=1/(x-2)
f(g(x))-вместо х надо подставить g(x)
f(g(x))=3-2*(1/(x-2)^3)=3-2/((x-2)^3)
f(f(x))-вместо х подставить f9x)
f(f(x))=3-2(3-x^3)^3
g(g(x))-в g(x) вместо х подставить g(x)
g(g(x))=1/(1/(x-2)-2)=(x-2)/(1-2x+4)=(x-2)/(5-2x)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
f(x)=3-2x^3; g(x)=1/(x-2)
f(g(x))-вместо х надо подставить g(x)
f(g(x))=3-2*(1/(x-2)^3)=3-2/((x-2)^3)
f(f(x))-вместо х подставить f9x)
f(f(x))=3-2(3-x^3)^3
g(g(x))-в g(x) вместо х подставить g(x)
g(g(x))=1/(1/(x-2)-2)=(x-2)/(1-2x+4)=(x-2)/(5-2x)